ANALYSIS OF LOGISTICS AND SUPPLY CHAIN MANAGEMENT AGILITY IN CORRUGATED BOX INDUSTRY - Yosef Daryanto; Klaus Krämer (Spektrum Industri: Jurnal Ilmiah Pengetahuan dan Penerapan Teknik Industri, 2016)
Several analyses were performed in this case study including the analysis of the business environments and the current supply chain system, which than followed by measurement and comparison of supply chain agility performance indicator. As corrugated box industry work in make/engineer to order system and by considering their competitive situation and uncertain business environment it was concluded that they need agility in their supply chain. The main problem was the unbalance power position with paper supplier that resulting low inbound inventory turns. Focusing on this weakness, two solutions were proposed; those are building higher collaboration with paper suppliers and performing better inventory management by set different inventory control and policy for each inventory class